Cesarean Section for Placenta Previa and Placenta Previa Accreta Spectrum - Takeda, Satoru; Takeda, Jun; Makino, Shintaro (The Surgery Journal, 2020)
According to the increase in the rate of cesarean section and the increase of high-aged pregnancy, we seem to more often encounter cases with placenta previa and placenta previa accrete spectrum. There are concerns about these cases, such as difficulty in controlling bleeding from the separation surface of placenta previa, the need for hysterectomy as a life-saving procedure, systemic management and hemostasis during massive hemorrhage, and treatment of disseminated intravascular coagulation (DIC). These cases are most frequently associated with cesarean hysterectomy.
Keywords: balloon tamponade; cesarean section; compression sutures; hysterectomy; placenta previa; placenta accreta spectrum